Research on the recycling of waste activated sludge as an adsorbent material for ammonium removal in wastewater - Thi, Thai Thanh Hoang; Thi, Truc Linh Do; Nguyen, Dai Hai (Vietnam Journal of Science and Technology, 2022)
Exploiting an inherently biological activity of natural compounds in Centella asiatica, a new hydrogel system with many beneficial properties was developed by a simple preparation. Gelatin-based hydrogels were in situ formed by Schiff base reaction to incorporate a Centella asiatica extract. The gelation time was controlled from 1 to more than 30 minutes by varying a composition ratio. The gelatin/aqueous Centella asiatica leaf extract-glutaraldehyde hydrogels exhibited microarchitecture and high porosity when being observed with a scanning electron microscope. The swelling ratio was reported in the range from 106% to 121%, which was an acceptable value for biomedical usage without any adverse effect on system blockage or stress. In addition, all hydrogels formed with more minor than or equal 0.5 wt% glutaraldehyde showed high cell compatibility; a Centella asiatica extract (≤ 1wt%) did not cause any effects on cell toxicity. Interestingly, the hydrogels composed of 2.5 wt% gelatin, 0.25 wt% extract, and 0.25 wt% glutaraldehyde gained 105% cell viability compared to standard culture conditions. Altogether, the gelatin/aqueous Centella asiatica leaf extract-glutaraldehyde hydrogels could become a promising candidate for tissue engineering and drug delivery platform.